Co-ligand tuned pyrimidine-2-carboxylate Mn(ii) complexes from a 2D 63 layer to an interpenetrated srs-net. Issue 26 (22nd June 2017) - Sun, Rui; Gao, Su-Mei; Wang, Shao-Qiang; Song, Wei-Chao; Zhao, Jiong-Peng; Liu, Fu-Chen
Abstract : Formate tuned chloride pyrimidine-2-carboxylate Mn(ii ) complexes from a 2D 6 3 layer to a polar 3D interpenetrated srs-net exhibit an obvious SHG response of approximately 0.8 × KH2 PO4 (KDP). Furthermore, 2 is an antiferromagnet with a field induced spin flop transition. Abstract : A 6 3 2D layer complex [Mn3 Cl3 (L 3 )] n ·H2 O (1 ) (L = pyrimidine-2-carboxylate) was obtained by assembling 2-cyanopyrimidine and manganese chloride, in which theL ligands were generated in situ . In1 six-membered Mn rings were constructed from Mn II ions andL ligands, which were connected to each other by double chloride anions affording a 2D layer. When the chloride anions in1 were substituted partly by formate, [Mn4 Cl3 L 4 (HCO2 )] n (2 ) was obtained. In2, theL ligands bridge Mn II to give a 1D chain, which was further connected by the double chloride anions and Cl/formate bridges to form a two-fold interpenetrated srs-net. Interestingly, 2 exhibits an obvious SHG response of approximately 0.8 times that of KDP. Furthermore, 2 is an antiferromagnet with a field induced spin flop transition.